Design, Molecular Docking, Synthesis, Characterization and Preliminary Evaluation of Novel 1,3,4-Oxadiazole Derivatives as Cyclin-Dependent Kinase 2 Inhibitors - Yousef Sabah Ali; Monther Faisal Mahdi; Basma Monjid Abd Razik; Talal Aburjai (Al-Mustansiriyah Journal of Pharmaceutical Sciences)
Novel 1,3,4-oxadiazole derivatives were designed, synthesized by reaction of semicarbazide hydrochloride with thiophene-2-carbaldehyde to form semicarbazone that undergo iodine-mediated cyclization to form 5-(thiophen-2-yl)-1,3,4-oxadiazol-2-amine which further reacted with different aldehydes to form Schiff base derivatives, and in-vitro tested for their cytotoxic activity. In a molecular docking study,